Factors that Determine the Market Value of Professional Football Players in Indonesia - Adiwiyana, Hajar Iman; Harymawan, Iman (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aims to identify the factors that determine the market value of professional football play- ers. The market value of soccer players is obtained from the official website www.transfermarkt.com which contains each professional soccer player’s prices in the transfer market. This study used 205 samples of professional football players in the Indonesian league in 2017. We analyzed this study using multiple linear regression and stepwise analysis with STATA 14 to see the factors that affect professional football players’ market value. The research results prove that age has a negative effect on the player’s market value, while assists, yellow cards, team status, and player status have a posi- tive impact on the player’s market value. On the other hand, goals, red cards, minutes played, and starting11 do not affect market value. Information about various factors that impact the market value of football players can support investment decisions in football club management. The results of this study add to the literature on human resource accounting studies, especially intangible as- sets. The character of football in Indonesia is classified as developing, even though most people are soccer fans, but it does not profit. There is no Indonesian football club that has taken the floor on the stock exchange, unlike in Europe. This study adds the variables Team Status and Player Status as a development of previous research. The determinants of market value can be used as additional information in the financial reporting of football clubs.